Prevalence and risk factors for Ureaplasma urealyticum infection among women of childbearing age, attending the Sino-Gabonese Friendship Hospital in Franceville, Southeast Gabon - Arnaud Brice Pambo-Pambo; Hilaire Moundounga Kenguele; Thiéry Ndong Mba; Ulrick Nzamba; Simon Mapasu (The Bioscan, 2025)
Ureaplasma urealyticum, an often asymptomatic intracellular bacterium, can cause urogenital disorders in both men and women. This study aimed to investigate the epidemiological and clinical profile of Ureaplasma urealyticum infection among women of childbearing age at the Sino-Gabonese Friendship Hospital in Franceville, Southeast Gabon. In a prospective cross-sectional study conducted between June and September 2024, a sample of women of childbearing age attending the Sino-Gabonese Friendship Hospital in Franceville completed a questionnaire on their medical and sociodemographic history and underwent vaginal swab collection. The presence of Ureaplasma urealyticum was detected using the MYCOFAST® Screening RevolutioN+ kit. Data were analyzed statistically using R software to identify factors associated with infection. Of the 164 women included, 26.21% (95% CI: [0.2, 0.34]) were positive for U. urealyticum. Statistical analyses showed that a history of sexually transmitted infections (STIs) (adjusted OR = 2.62, 95% CI: [1.08, 6.37], p = 0.034) and lack of contraception (adjusted OR = 3.22, 95% CI: [1.3, 7.97], p = 0.012) were significantly associated with an increased risk of infection. These findings highlight the importance of screening for U. urealyticum in women, particularly those with a history of STIs or who do not use contraception. Targeted prevention programs, including sexual education campaigns and systematic screening, are needed to reduce the prevalence of this infection and its impact on reproductive health.